Structure–activity relationships in hydroxy-2,3-diarylxanthone antioxidants. Fast kinetics spectroscopy as a tool to evaluate the potential for antioxidant activity in biological systems - Santos, Clementina M.M. (2011)
A structure–activity relationship has been established for eight hydroxy-2,3-diarylxanthones (XH) bearing hydroxy groups on the two aryl rings. One-electron oxidation by superoxide radical-anions (ΣO2 -) and ΣTrp radicals as well as reaction with ΣCCl3O2 and ΣCHCl2O2 radicals demonstrates that two OH groups are required for efficient antioxidant reactivity in cetyltrimethylammonium bromide micelles. Hydroxy groups at the meta and para positions on either of the two phenyl rings confer enhanced reactivity, but XH bearing an OH at the para position of either phenyl ring is unreactive. While oxidation is favoured by OH in both meta and para positions of 2-aryl xanthone substituents, addition of a third and/or fourth OH enhances electron-donating capacity. In Cu2+-induced lipid peroxidation of human LDL, the lag period preceding the commencement of lipid peroxidation in the presence of XH bearing OH at meta and para positions on the 3-phenyl ring is extended to twice that observed with a comparable concentration of quercetin, a reference antioxidant. These antioxidants are also superior to quercetin in protecting human skin keratinocytes against tert-butylhydroperoxideinduced oxidative stress. While XH antioxidant activity in model biological systems is consistent with the structure–activity relationship, their response is also modulated by the localization of XH and by structural factors.